Pengaruh Model Pembelajaran Make a Match Berbantuan Media Diorama Terhadap Hasil Belajar Peserta Didik Pada Materi Siklus Air Di Kelas V SDN 62 Banda Aceh - Ulfia Ulfia; Intan Safiah; Suci Fitriani (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
This study entitled The Effect of Make A Match Learning Model Assisted by Diorama Media on Student Learning Outcomes on Water Cycle Material in Class V SDN 62 Banda Aceh. The formulation of the problem in this study is "is there a significant effect of the make a match learning model assisted by diorama media on student learning outcomes on the water cycle material in class V SDN 62 Banda Aceh?". This study aims to determine the effect of the make-a-match learning model assisted by diorama media on student learning outcomes on the water cycle material in class V SDN 62 Banda Aceh. The research uses a  quantitative approach.  This type of research is  True Experimental with Posttest Only Control design. The research was conducted at  SDN   62   Banda   Aceh in  Cot  Mesjid   Village. Sampling used the Random Sampling technique with a total of 62 students in class VA and VB. The data collection technique used a posttest test, while the data analysis technique used an independent t-test and SPSS Statistics 24. The results of hypothesis testing obtained a significance value (2-tailed) of 0.000  0.05. Then the decision criteria are  H_a  accepted and  H_0  rejected.  It can  be concluded  that  there  is  a  significant effect  of  using  the  Make A  Match learning model assisted by Diorama media on student learning outcomes on the water cycle material in class V SDN 62 Banda Aceh